The Role of Training and Career Development on the Quality of Work - Sri Rahayu; Pompong Budi Setiadi; Riska Agustina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Training is a systematic process of an organization aimed at developing individual skills, abilities, knowledge or attitudes that can change employee behavior in achieving company goals that have been set. Career development is a continuous process in which individuals go through personal efforts to realize career planning goals that are adapted to organizational conditions. Employee performance is the result of an assigned job in an organization. This study aimed to determine the role of training and career development on the quality of work through its competence as an intervention. The research method used is qualitative. The study results can be concluded that training and career development have a role in the quality of work. It can be seen that training and career development indirectly influence the quality of work.